Validación de un programa basado en el manejo de residuos sólidos para desarrollar actitudes ambientales en los estudiantes de la I.E Jenaro Ernesto Herrera Torres - Tongo Guevara, Magaly (2014)
The objective of this research was to implement a program based on salid waste management to develop environmental attitudes in the students of the "Jenaro Ernesto Herrera Torres" Educational lnstitution. In this sense, the attitudes were measured components in their cognitiva, affective and reagent. According to the literatura review was formulated the research hypotheses under the assumption that the students will develop their environmental attitudes if the program is applied, the same that was composed of experiential workshops, the- same- that were applied toa random sample of 30 students from the educational institution. In the methodological level, the applied type research was conducted under a pre experimental design, to which group of students were given a pre and post test to determine differences in the development of their attitudes. The test consisted of 37 questions, 17 of which corresponded to the cognitive component, 4 the affective component and 16 to the reactive component. The answers to the items were designed under scale semantics and whose valuation was from 1 to 5 depending on the importance of the response. In terms of the hypothesis test, for verification was used the test of the difference paired corresponding to the normal distribution with a confidence level of 95 %, arriving to be demonstrated that with the implementation of the program based on the solid wastetreatment, the students of the Educational lnstitution "Jenaro Ernesto Herrera Torres" developed favorable environmental attitudes. With regard to the components of environmental attitudes, both in the cognitive component, reactive and emotional, the students also showed improvement in regard to the development favorable environmental attitudes, which was proved when performing the comparison of the results obtained in both the pretest and the posttest. Key words: solid waste management, experimental design.